Knowledge, attitude, and performance of the universal precautions by nursing students of the Faculty of Nursing, Prince of Songkla University - W Kongsuwan; B Oearsakul; Y Matchim (Journal of Health Science and Medical Research (JHSMR), 2004)
This descriptive study aimed to identify knowledge, attitude and performance (KAP) of the universal precautions (UPs) in clinical practice of nursing students of the Faculty of Nursing, Prince of Songkla University. The sample comprised 246 third and fourth year nursing students in academic year 2002. The data was collected using questionnaires and participatory observation from October 2002 to February 2003. The results of the research revealed that during the previous year, 31% of the participants experienced needlestick injuries and sharp instrument accidents, and 24.30% were exposed to blood or secretion. According to the results of the survey using the questionnaires, the participants were highly knowledgeable about the UPs. Also, they showed good attitude towards and good performance at UPs. The result of participatory observation illustrated that 45% of the participants washed their hands before touching patients, while 53% washed their hands after providing care to patients. In addition, seventy to ninety-eight percents of the participants used protective devices, such as wearing gloves and masks, to protect themselves from contamination with blood and body fluid. In order to prevent needlestick injuries, the participants did not recap, recapped with one hand and recapped with both hands at the percentages of 47%, 60% and 30%, respectively. However, the correlation between Ups performance self-report done by students and observation of students' applying the UPs technique carried out by clinical instructors was not significant.